Dehydropolymerisation of Methylamine Borane and an N‐Substituted Primary Amine Borane Using a PNP Fe Catalyst. Issue 35 (28th May 2020) - Anke, Felix; Boye, Susanne; Spannenberg, Anke; Lederer, Albena; Heller, Detlef; Beweries, Torsten
Abstract: Dehydropolymerisation of methylamine borane (H3 B⋅NMeH2 ) using the well‐known iron amido complex [(PNP)Fe(H)(CO)] (PNP=N(CH2 CH2 P i Pr2 )2 ) (1 ) gives poly(aminoborane)s by a chain‐growth mechanism. In toluene, rapid dehydrogenation of H3 B⋅NMeH2 following first‐order behaviour as a limiting case of a more general underlying Michaelis–Menten kinetics is observed, forming aminoborane H2 B=NMeH, which selectively couples to give high‐molecular‐weight poly(aminoborane)s (H2 BNMeH) n and only traces of borazine (HBNMe)3 by depolymerisation after full conversion. Based on a series of comparative experiments using structurally related Fe catalysts and dimethylamine borane (H3 B⋅NMe2 H) polymer formation is proposed to occur by nucleophilic chain growth as reported earlier computationally and experimentally. A silyl functionalised primary borane H3 B⋅N(CH2 SiMe3 )H2 was studied in homo‐ and co‐dehydropolymerisation reactions to give the first examples for Si containing poly(aminoborane)s. Abstract : Getting poly(aminoborane)s : The well‐known Fe amido complex [(PNP)Fe(H)(CO)] (PNP=N(CH2 CH2 P i Pr2 )2 ) is a potent catalyst for the selective formation of poly(aminoborane)s from methylamine borane and a SiMe3 ‐substituted analogue. Mechanistic studies support a chain‐growth mechanism with polymer formation by nucleophilic attack at the terminus of a growing B−N chain.